AN ASSESSMENT OF THE LEVEL OF HIV/AIDS AWARENESS AND VULNERABILITY IN STATE-OWNED TERTIARY INSTITUTIONS OF BAUCHI NIGERIA - Sani Babaji (International Studies Journal)
This study was conducted on students of tertiary institutions of Bauchi state which include universities, polytechnics and monotechnics, specifically students of Abubakar Tatari Ali Polytechnic, A.D. Rafa'i College of Legal and Islamic Studies, and Bauchi State University, Gadau. The researcher collected data using both qualitative and the quantitative methods. The first set of datum were made up of surveys(questionnaires)administered on students, while the second set is the qualitative datum obtained from the students using Focus Group Discussions( FGDs).The third set of the datum was obtained from the medical offices and students' affairs of the various institutions using in[1]depth- interviews(IDIs).The study populations are the entire students of Tertiary institutions in Bauchi State including both male and females students at different level of Educational program. In order to acquire objective and reliable data, the researcher adopted multistage method of sampling where the samples of the tertiary institution were selected, Stratified sampling was used to divide the Tertiary institutions in Bauchi State were divided into three strata namely; while simple random samplings were used to selects the samples of the faculties as well as the samples of the departments and the entire samples of the students for the research. Therefore, the target population for the study consists of all students of the state-owned tertiary institutions of Bauchi state. Others are students' affairs officers of the various institutions and medical officers of the various institutions including nurses and doctors. The findings of the research revealed that there is awareness of HIV/AIDS among students of tertiary institutions among students in the study are, there is relationship between awareness and preventive measures of HIV/AIDS, however it was also found that there is no relationship between the awareness of HIV/ADS and program of study among the students of the state-owned tertiary institution of the state.